2023
DOI: 10.3390/socsci12020103
|View full text |Cite
|
Sign up to set email alerts
|

Work Adjustment in an Employment Program for Colombian People Involved in Armed Conflict: A Multilevel Mixed-Methods Case Study

Abstract: Work plays a significant role in societies; however, currently, work is a particularly difficult area for those in the most vulnerable social categories who have been heavily affected by the COVID-19 pandemic. Because there is scarce research on labor integration of people affected by armed conflicts from work adjustment (WA) perspectives, we have developed research to understand the relationship between people and their work setting in an employment program inspired in supported employment models (SEMs). To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This theory, according to Scheneider (Neuenschwander & Hofmann, 2022), looks more into career selection patterns and is a process of improvement and adjustment between the individual Person who seeks adjustment to his work environment. The aspect of work environment with employees and the relationship between the two can be described as a form of harmonious relationship between employees and their work environment, and vice versa and a complementary relationship between individuals and the environment (Antón Rubio et al, 2023). Furthermore, Brown (Dalgic & Akgunduz, 2022) suggested that work adjustment theory includes a level of theory known as P (Person) and E (Environment) theory.…”
Section: Figure 2 Age and Field Of Work By Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…This theory, according to Scheneider (Neuenschwander & Hofmann, 2022), looks more into career selection patterns and is a process of improvement and adjustment between the individual Person who seeks adjustment to his work environment. The aspect of work environment with employees and the relationship between the two can be described as a form of harmonious relationship between employees and their work environment, and vice versa and a complementary relationship between individuals and the environment (Antón Rubio et al, 2023). Furthermore, Brown (Dalgic & Akgunduz, 2022) suggested that work adjustment theory includes a level of theory known as P (Person) and E (Environment) theory.…”
Section: Figure 2 Age and Field Of Work By Gendermentioning
confidence: 99%
“…This theory is to know P as an individual or employee while E is the work environment or organization, the point of compatibility between the two, and the interaction that occurs between P and E. These P and E variables are often used to explain behavior or outcomes (Neuenschwander & Hofmann, 2022). However, the basic proposition of PE theory research (Antón Rubio et al, 2023), explained as behavior or behavioral outcomes do not lie so much in the P variable or the E variable, but rather lies in the combination of P and E to be able to explain and predict work behavior and work outcomes. Interaction refers to P and E, actions and reactions to each other in a give and take.…”
Section: Figure 2 Age and Field Of Work By Gendermentioning
confidence: 99%